THE STRATEGIC COMPETENCE OF VOCATIONAL SCHOOL STUDENTS IN SOLVING ARITHMETIC ROW AND SERIES PROBLEMS IS REVIEWED FROM COGNITIVE STYLE - Nur Muawaliana; Dwi Juniati; Agung Lukito (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This study describes the strategic competence of vocational high school students in solving arithmetic sequence and series problems based on their cognitive styles: Field Independent (FI) and Field Dependent (FD). Four indicators of strategic competence were examined formulating, representing, solving, and evaluating problems. Using a qualitative descriptive approach, the study involved four Grade X Software Engineering students from SMKN 4 Bojonegoro, selected purposively through the Group Embedded Figures Test (GEFT). Data were collected through problem-solving tests and in-depth interviews, then analyzed using the Miles and Huberman model with source triangulation. The findings show that FI students exhibit strong strategic competence across all indicators: they can systematically formulate information, construct accurate mathematical representations, apply flexible solution strategies, and evaluate processes reflectively. In contrast, FD students demonstrate limited strategic competence, relying heavily on examples, producing mechanical representations, and showing minimal self-evaluation. These results highlight the significant influence of cognitive style on students' strategic thinking. The study suggests that mathematics teachers should adapt instruction by providing open-ended tasks, conceptual scaffolding, and reflective activities to support strategic competence development, especially for FD learners.